Data quality assurance in international supply chains: an application of the value cycle approach to customs reporting. Issue 2 (3rd May 2016) - Wang, Yuxin; Hulstijn, Joris; Tan, Yao-Hua
Abstract : With increasing international trade and growing emphasis on security and efficiency, enhanced information and data-sharing between different stakeholders in global supply chains is required. Currently, data quality is not only problematic for traders, but also for various government agencies that are involved in border control, such as customs authorities, food and health inspection agencies, or border force. We adapt principles from the value cycle modelling in accounting, and show how these principles enabled by ICT can be extended to supply chain management to ensure quality of data reported to customs. We then describe a typical application scenario based on a real but anonymized case, to show that value cycle monitoring can be applied (feasibility), and if applied, what the expected benefits are (usefulness).